Lack of eutrophication in a tallgrass prairie ecosystem over 27 years - McLauchlan, Kendra K.; Craine, Joseph M.; Nippert, Jesse B.; Ocheltree, Troy W. (My University, 2014)
Many North American grasslands are receiving atmospheric nitrogen (N) deposition at rates above what are considered critical eutrophication thresholds. Yet, potential changes in grassland function due to anthropogenic N deposition are poorly resolved, especially considering that other dynamic factors such as land use and precipitation can also affect N availability. To better understand whether elevated N deposition has altered ecosystem structure or function in North American grasslands, we analyzed a 27-year record of ecophysiological, community, and ecosystem metrics for an annually burned Kansas tallgrass prairie. Over this time, despite increasing rates of N deposition that are within the range of critical loads for grasslands, there was no evidence of eutrophication. Plant N concentrations did not increase, soil moisture did not decline, forb diversity did not decline, and the relative abundance of dominant grasses did not shift toward more eutrophic species. Neither aboveground primary productivity nor N availability to plants increased. The fates of deposited N in grasslands are still uncertain, and could include management losses through burning and grazing. However, evidence from this grassland indicates that eutrophication of North American grassland ecosystems is not an inevitable consequence of current levels of N deposition.
Keywords: Eutrophication; Grassland; Konza Prairie; Nitrogen deposition; Precipitation; Tallgrass prairie